A Proficiency Based Stepwise Endovascular Curricular Training (PROSPECT) Program Enhances Operative Performance in Real Life: A Randomised Controlled Trial. (September 2017) - Maertens, H.; Aggarwal, R.; Moreels, N.; Vermassen, F.; Van Herzeele, I.
Abstract: Objectives: Healthcare evolution requires optimisation of surgical training to provide safe patient care. Operating room performance after completion of proficiency based training in vascular surgery has not been investigated. Design: A randomised controlled trial evaluated the impact of a Proficiency based Stepwise Endovascular Curricular Training program (PROSPECT) on the acquisition of endovascular skills and the transferability of these skills to real life interventions. Materials: All subjects performed two endovascular interventions treating patients with symptomatic iliac and/or superficial femoral artery stenosis under supervision. Primary outcomes were technical performances (Global Rating Scale [GRS]; Examiner Checklist), operative metrics, and patient outcomes, adjusted for case difficulty and trainee experience. Secondary outcomes included knowledge and technical performance after 6 weeks and 3 months. Methods: Thirty-two general surgical trainees were randomised into three groups. Besides traditional training, the first group ( n = 11) received e-learning and simulation training (PROSPECT), the second group ( n = 10) only had access to e-learning, while controls ( n = 11) did not receive supplementary training. Results: Twenty-nine trainees (3 dropouts) performed 58 procedures. Trainees who completed PROSPECT showed superior technical performance (GRS 39.36 ± 2.05; Checklist 63.51 ± 3.18) in real life with significantly fewer supervisor takeovers compared with trainees receiving e-learning alone (GRS 28.42 ± 2.15; p = .001; Checklist 53.63 ± 3.34; p = .027) or traditional education (GRS 23.09 ± 2.18; p = .001; Checklist 38.72 ± 3.38; p = .001). Supervisors felt more confident in allowing PROSPECT trained physicians to perform basic ( p = .006) and complex ( p = .003) procedures. No differences were detected in procedural parameters (such as fluoroscopy time, DAP, procedure time, etc.) or complications. Proficiency levels were maintained up to 3 months. Conclusions: A structured, stepwise, proficiency based endovascular curriculum including e-learning and simulation based training should be integrated early into training programs to enhance trainee performance.